2009
DOI: 10.1111/j.1464-5491.2009.02710.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Type 2 diabetes to the prevalence, incidence and progression of age‐related hearing loss

Abstract: Type 2 diabetes was associated with prevalent, but not incident hearing loss in this older population. Accelerated hearing loss progression over 5 years was more than doubled in persons newly diagnosed with diabetes. These data explore further reported links between Type 2 diabetes and age-related hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
139
6
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(163 citation statements)
references
References 14 publications
8
139
6
10
Order By: Relevance
“…Sunkum et al 9 found prevalence of hearing loss in 58.3% of patients with controlled glucose and 85.2% of diabetic patients with uncontrolled glucose levels, corroborating with the hypothesis that the glucose control can protect against hearing deficiency 23,29 . Study realized in diabetic patients with early diagnosis (before 40 years old) showed prevalence of 21.7% sensorioneural uni or bilateral hearing loss, stating that the type 2 DM early start and with poor glycemic control leads to an increased prevalence of subclinical hearing loss and prejudice in the responses of the brain stem 13 .…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Sunkum et al 9 found prevalence of hearing loss in 58.3% of patients with controlled glucose and 85.2% of diabetic patients with uncontrolled glucose levels, corroborating with the hypothesis that the glucose control can protect against hearing deficiency 23,29 . Study realized in diabetic patients with early diagnosis (before 40 years old) showed prevalence of 21.7% sensorioneural uni or bilateral hearing loss, stating that the type 2 DM early start and with poor glycemic control leads to an increased prevalence of subclinical hearing loss and prejudice in the responses of the brain stem 13 .…”
Section: Discussionmentioning
confidence: 52%
“…Mitchell et al 23 results found in a consistent cross association between the duration of diabetes and hearing loss, revealing that in 5 years, there was an accelerated progression of deafness in patients early diagnosed with DM. However, in the same study, people with previously diagnosed diabetes showed a non-significant inverse association with the progression of hearing loss.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The cross sectional study done by Shafeeqet. al., [11] in 2015 on 83 patients of type 2 DM patients reported the prevalence as 62.65%.The mean age of cases and controls in our study was 61.82 years and 60.86 years respectively.…”
Section: Discussionmentioning
confidence: 84%
“…Shafeeqet. al., in 2015 [11] also showed that diabetics with uncontrolled sugar levels (HbA1c >8%) had increased prevalence of sensorineural hearing loss (76.6%) when compared with diabetics of moderately (68.1%) and well controlled (45.1%) sugar levels. However, 2011 study by Rajendranet.…”
Section: Discussionmentioning
confidence: 99%